2022
DOI: 10.3390/ijerph19127399
|View full text |Cite
|
Sign up to set email alerts
|

Use of Generalized Weighted Quantile Sum Regressions of Tumor Necrosis Factor Alpha and Kidney Function to Explore Joint Effects of Multiple Metals in Blood

Abstract: Exposure to heavy metals could lead to adverse health effects by oxidative reactions or inflammation. Some essential elements are known as reactors of anti-inflammatory enzymes or coenzymes. The relationship between tumor necrosis factor alpha (TNF-α) and heavy metal exposures was reported. However, the interaction between toxic metals and essential elements in the inflammatory response remains unclear. This study aimed to explore the association between arsenic (As), cadmium (Cd), lead (Pb), cobalt (Co), copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…TNF-α can activate three diverse pathways: mitogen-activated protein kinase (MAPK), NF-κB, and cell death signaling pathways. The current results agree with the previously reported results [ 46 ]. In this study, RJ and P diminished the inflammatory markers’ elevation, mainly due to their phenolic mixes and other minor constituents [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 94%
“…TNF-α can activate three diverse pathways: mitogen-activated protein kinase (MAPK), NF-κB, and cell death signaling pathways. The current results agree with the previously reported results [ 46 ]. In this study, RJ and P diminished the inflammatory markers’ elevation, mainly due to their phenolic mixes and other minor constituents [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 94%
“…These metals are associated with adverse health effects, including sarcopenia, osteoporosis, kidney damage, etc. 5 7 . Previous studies have reported that exposure to As, Cd, cobalt (Co), Pb, and mercury (Hg) could cause chronic diseases such as diabetes and obesity 8 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Metals are associated with adverse health effects, sarcopenia, osteoporosis, kidney damage, etc [5][6][7]. Previous studies have reported that exposure to As, Cd, cobalt (Co), Pb, and mercury (Hg) could cause chronic diseases such as diabetes and obesity [8][9][10].…”
Section: Introductionmentioning
confidence: 99%